ANALYSIS OF FACTORS AFFECTING PROFIT MANAGEMENT IN INDONESIA - Ria Karina; Annisya Taherah (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Earnings management is a management action taken in relation to financial reporting that tries to benefit managers or management. The frequency of events makes creditors question the veracity of rumors that financial accounts contain information. This study tries to determine whether the debt-to-asset ratio, audit type, and audit partner are female. Negative net income, cash flow operational to assets versus earnings management, and return on assets. In order to process the data for this study, Eviews software was used to collect information from enterprises in the health sector, basic materials, non-cyclical consumers, energy, infrastructure, property, and real estate from 2017 to 2021. Test the descriptive statistics of a data before examining the regression panel data. The analysis's findings show that there is a relationship between the type of auditor and earnings management; however, the other factors, including female audit partners, firm size, debt-to-asset ratio, return on asset, cash flow operations to assets, and negative net income with management, claim there is no relationship. profit. This is due to the fact that the best audit a company can use will reduce the likelihood of earnings management by managers, but even though the company is large, using earnings management is still possible, and even though women are given more consideration, it is still possible to resolve earnings management. The incidence of earnings management cannot be reduced by the debt to asset ratio, which measures liquidity, or the return on assets, which measures profitability.